PERAN LITERASI EKONOMI DALAM MENINGKATKAN PEMBELAJARAN SISWA PADA ERA GLOBALISASI 5.0 DI SMA KARTIKA I-2 MEDAN - Siahaan, Nova Yunita Sari; Nababan, Netty Winda Sari; Simbolon, Iindola (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2024)
This community service (PKM) is focused on the Role of Economic Literacy in Improving Student Learning in the Era of Globalization 5.0 at SMA Kartika I-2 Medan. The implementation of this PKM is motivated by the low skills of students in utilizing information technology and multimedia. The objectives to be achieved in this PKM include: 1) providing an understanding to students of SMA Kartika I-2 Medan so that they can utilize technology positively, 2) helping students to see business opportunities in the digital era, 3) providing an understanding to students related to current digital technology, 4) training students to Implement Economic Literacy well 5) fostering cooperation with various parties related to Community Service, especially the school, to introduce HKBP Nommensen Medan University to students at SMA Kartika I-2 Medan. The method used to achieve the objectives of this PKM is through lectures and practices. Materials related to the training are delivered through lectures and discussions. Then the training is carried out directly with direct practice. This PKM activity overall got good and satisfying results. Some components that were successfully achieved in the implementation of this activity include: 1) achievement of activity objectives, 2) achievement of planned material targets.